2014
DOI: 10.1007/s00508-014-0597-2
|View full text |Cite
|
Sign up to set email alerts
|

Emergency (clonal spread) of methicillin-resistant Staphylococcus aureus (MRSA), extended spectrum (ESBL) – and AmpC beta-lactamase-producing Gram-negative bacteria infections at Pediatric Department, Bosnia and Herzegovina

Abstract: Pediatric infections caused by clonal spread of MRSA and beta-lactamase-producing Gram-negative bacteria are of major concern. Proper infection control measures should be implemented in order to avoid the transmission and major outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The most prevalent culture sites were the umbilicus and SSI. In human medicine, only a few reports describe 3GCRE umbilical infections [52][53][54]. In contrast, in neonatal foals, several studies have described or reported 3GCRE isolation from the umbilicus [16,18,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent culture sites were the umbilicus and SSI. In human medicine, only a few reports describe 3GCRE umbilical infections [52][53][54]. In contrast, in neonatal foals, several studies have described or reported 3GCRE isolation from the umbilicus [16,18,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…AmpC β-lactamases, which confer resistance against a broad range of substrates, are less prevalent than ESBL but still a growing issue, having been identified in several outbreaks (Roh et al, 2008; Mansouri et al, 2014; Uzunovic et al, 2014; Kameyama et al, 2015). Multiple factors contribute to the severity of this problem, including the fact that these enzymes confer resistance to carbapenems when combined with decreased outer membrane permeability (Philippon et al, 2002; Woodford et al, 2007) and that they are not neutralized by ESBL inhibitors, which limits the possible phenotypic diagnostic and therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%